Effectiveness of Online Learning Using Online Media During The Covid-19 Pandemic in Islamic Religious Education Learnings - Karmin (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This study aims to see a strong picture of bold learning using online media during the Covid-19 Pandemic in Islamic Education subjects. This research is a descriptive quantitative study that focuses on evaluating learning using online media. The study population was all students of SMA Negeri 20 Jakarta who was taught in Islamic Education subjects using a bold method. The research sample of students of class XI MIPA 1 SMA Negeri 20 Jakarta was selected using a simple random sampling technique by considering population homogeneity. The data instrument used an online learning questionnaire. Data analysis using descriptive statistics. The results of the study illustrated that the students in the assessment of Islamic Education learning using online media were very effective (23.3%), most of them rated it as effective (46.7%), and the assessment was normal (20%). Although there are also students who think learning is ineffective (10%), and absolutely none (0%) think it is very ineffective. Finally, to improve the quality of learning that dared PAI during the Covid-19 pandemic, educators had to fulfill ten suggestions from respondents, namely: (1) learning was carried out through video calls; (2) providing brief learning materials; (3) minimize sending material in the form of heavy videos to maintain quotas; (4) the selection of material in the video must be based on language criteria that are easily implemented; (5) continue to provide material before the assignment; (6) presents varied and different questions for each student; (7) presenting the assignment must include how it works; (8) assign assignments according to the lesson schedule; (9) remind students if there is a task given; and (10) reducing tasks.